Investigating Indoor Air Quality in UAE Restaurants: A Case Study - Priji Biju (2025)
Particulate matter, oxides of carbon and volatile organic compounds released during cooking can have a harmful impact on the health of employees and clienteles of restaurants. Hence it is crucial to monitor and maintain a healthy indoor air quality (IAQ) of restaurants and this study intends to assess the parameters of indoor air quality of a busy restaurant in Dubai with the intention to offer recommendations to enhance the indoor environment of the restaurant. Following a preliminary assessment and quantitative walk-through inspection of the kitchen and dining area, a survey was administered to the restaurant's staff and patrons in order to determine quality of interior environment. The responses received for the employees’ survey emphasised the areas of concern as well as the variables that needed to be assessed and monitored in order maintain the indoor air quality at desired levels. Using the compatible instruments, parameters such as PM2.5, PM10, Temperature, Humidity, Interior Lighting, CO2, CO, and Total VOCs were measured to evaluate the indoor air quality. While analysing the results it was observed that cooking activities in the kitchen are producing particulate matter to an undesired level and augmentation of ventilation is required to maintain a healthy working atmosphere for the employees. Customer response was satisfactory on the quality of indoor environment of the restaurant as per Likert 5-point analysis.